2017
DOI: 10.20944/preprints201704.0173.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon Stocks across a Fifty Year Chronosequence of Rubber Plantations in Tropical China

Abstract: Transition from forest to rubber (Hevea brasiliensis Muell. Arg.) plantation has occurred in tropical China for decades. Rubber has been planted on 1 million ha to provide raw materials to the rubber industry. The role of various-aged rubber plantations in carbon (C) sequestration remains unclear. The biomass C accumulation including latex C and C distribution in soil of five different-aged stands (7, 13, 19, 25 and 47 years old) were examined. The total biomass C stock (TBC) and total net primary productivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In this study, the litter production increased from the 12‐ to the 32‐year plantation and decreased from the 32‐year to the 49‐year plantation (Table ). Thus, we can speculate that mature rubber plantations may have greater NPP than young and old‐growth rubber plantations, which was also reported by a recent study in rubber plantations of different stand age in Xishuangbanna (Liu et al, ). Furthermore, the relatively higher tree density may also lead to greater photosynthate transported to root systems in mature plantations (Table ), and hence show higher root activities and root respiration, giving rise to the R A variation among different stands.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In this study, the litter production increased from the 12‐ to the 32‐year plantation and decreased from the 32‐year to the 49‐year plantation (Table ). Thus, we can speculate that mature rubber plantations may have greater NPP than young and old‐growth rubber plantations, which was also reported by a recent study in rubber plantations of different stand age in Xishuangbanna (Liu et al, ). Furthermore, the relatively higher tree density may also lead to greater photosynthate transported to root systems in mature plantations (Table ), and hence show higher root activities and root respiration, giving rise to the R A variation among different stands.…”
Section: Discussionsupporting
confidence: 82%
“…This means that most of the rubber plantations will become old-growth stands that need to be felled and replanted in the coming two decades. Although the total ecosystem C storage will increase with increasing stand age (Liu et al, 2017), our results showed that increasing R S with increasing stand age will partly offset the increased soil C storage, keeping it relatively stable in the long term. Therefore, the effect of stand age on rubber plantation C exchange and soil C dynamics should be evaluated in future studies estimating regional/global-scale rubber plantation C storage.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations